(untitled) - Balowria, Kamaldeep Singh; Syed, Masooma; Tousia, Sheikh; Faruqi, Nafis Ahmad (Academia Anatomica International, 2019)
Introduction: Methotrexate, a folic acid antagonist is used as a first line drug for the treatment of a number of malignancies and immune disorders like rheumatoid arthritis. Due to hepatoxicity its dose needs to be monitored and sometimes it has to be stopped. In the present study we intend to do a detailed histopathological investigation after methotrexate toxicity on the relatively neglected organ i.e. kidney of rat. Subjects and Methods: Albino rats were divided into four groups (1, 2, 3, and 4) of six animals each. Control group 1 was given distilled water whereas experimental groups 2, 3, and 4 were given low, therapeutic and high doses of methotrexate orally for 28 days. Results: The results showed congestion and infiltration of the glomeruli and interstitial edema and tubular degeneration which were dose dependent. Conclusion: The degenerative changes necessitate extra precautions to be taken while using drug for prolonged period. The study merits due to great social impact.